Brand Experience and Identification Impact on Loyalty Via Brand Love Among Gen Z iPhone Users - Rayie Tariaranie Wiraguna; Ahmad Mukimul Khaq’qi; Safira Rusyda Azizah (Jurnal Manajemen dan Kewirausahaan, 2025)
The advancement of technology has contributed to the increasing trend of second-hand iPhone usage among generation Z (Gen Z), especially in Malang City. This study aims to examine the mediating role of brand love in the relationship between brand experience and consumer brand identification on brand loyalty. A quantitative approach was employed using a survey method with 190 Gen Z respondents who use second-hand iPhones, selected through purposive sampling. The research focuses on understanding the emotional and psychological factors that influence consumers' attachment and loyalty toward brands, even in the context of used products. The findings reveal that brand experience and consumer brand identification have a significant and positive influence on both brand love and brand loyalty. Furthermore, brand love acts as a significant mediator in strengthening the relationship between the independent variables and brand loyalty. These results highlight the importance of emotional bonds in shaping consumer behavior, especially among younger generations who seek identity and expression through the brands they use. The study provides practical implications for marketers of second-hand smartphones, especially Apple resellers, to build stronger engagement strategies by emphasizing identity alignment and emotional experience.